(untitled) (Nexus International Journal of Science and Education, 2024)
This study explored the teacher’s Multiple roles of Teacher-Parents balancing the family and classroom responsibilities Specifically, it aims to answer the experiences of teachers doing dual roles as parent and teacher at the same time and the coping mechanisms on the challenges emerging of juggling multiple roles. To achieve the objectives of the study, I made use of phenomenology. The 10 participants of this study are from Kapitan Tomas Monteverde Sr. Central Elementary School SPED Center. I used a semi-structured online interview using the coding technique in analyzing the data. The study disclosed different themes such as Difficulty in navigating dual roles and Managing emotions. Another theme is Coping with the challenges in collecting results sub-themes: Establishing boundaries and Fostering supportive classroom environment. With these themes revealed Parents who are also teachers struggle to strike a balance between their personal and professional obligations. If not handled properly, this may result in stress and burnout. Schools can assist these educators by offering flexible work schedules and work-life balance professional development. Teachers need to know how to look after themselves. This may seem a simple and easy task; however, when faced with a multitude of teaching tasks, one of the areas all teachers can miss, is taking care of themselves. Understanding and supporting teacher well-being in schools, and enabling teachers to support themselves, is essential for a sustained healthy learning environment.